Aptness of Beauveria bassiana and enhanced diatomaceous earth (DEBBM) for control of Rhyzopertha dominica F - Wakil, Waqas, University of Agriculture, Faisalabad, Pakistan; Riasat, Tahira, University of Agriculture, Faisalabad, Pakistan; Ghazanfar, M. Usman, University of Sargodha, Pakistan; Kwon, Y.J., Kyungpook National University, Daegu, Republic of Korea; Shaheen, Farid Asif, Pakistan Science Foundation, Islamabad, Pakistan (Entomological research, 2011)
A diatomaceous earth formulation enhanced with bitterbarkomycin (DEBBM) combined with Beauveria bassiana (Balsamo) Vuillemin was evaluated against lesser grain borer Rhyzopertha dominica F. (Coleoptera: Bostrychidae) under laboratory conditions. DEBBM was applied at the rates of 15 and 30 ppm alone as well as in combination with 6.69 × 10∨6, 6.69 × 10∨8 and 6.69 × 10∨10 conidia/kg of wheat. Mortality of treated adults was recorded after 5, 10 and 15 days of exposure. Bioassays were carried out at 20, 25 and 30℃ with 55 and 75% relative humidity. The emergence of progeny was also assessed 60 days post exposure. The combined use of DEBBM and B. bassiana considerably increased adult mortality especially at increasing temperatures and longer exposure intervals compared with DEBBM and B. bassiana alone. Progeny production was less in wheat treated with high dose rates of DEBBM +B. bassiana. The per cent mycosis in the cadavers was maximum where B. bassiana was applied at low dose rates. The results of the present study indicated that a combination of DEBBM and B. bassiana may provide effective control of R. dominica.